Piracy and Quality Choice in Monopolistic Markets - Matteo Alvisi; Elena Argentesi; Emanuela Carbonara (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We study the impact of piracy on the quality choices of a monopolist. In the absence of piracy, the monopolist has no incentive to differentiate its products. With piracy the monopolist might instead produce more than one quality, so that differentiation arises as the optimal strategy. This is because the producer wants to divert consumers from the pirated good to the original one. Differentiation involves either producing a new, low-quality good such that piracy is either eliminated or still observed in equilibrium.
Keywords: 330